2023
DOI: 10.51535/tell.1283101
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Problematic Technology Use and Mental Health Problems in the COVID-19 Pandemic: A Meta-Analysis

Abstract: Objective: The COVID-19 pandemic has had a negative impact on individuals both psychologically and socially. The current research shows that problematic technology use and mental health problems increased during the pandemic period. Method: In this study, studies examining the relationship between problematic technology use and mental health problems in the COVID-19 pandemic were examined and a meta-analysis was conducted. The present meta-analysis focused on the problematic technology use (i.e., intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…A systematic study was conducted by Hamarta et al, (2021) using terms such as internet addiction, psychoeducation etc.. As a result of this study, it was concluded that the experimental attempts made on internet addiction were effective on one of the sub-dimensions of technology addiction. Considering the results of a systematic analysis examining the programs prepared to prevent internet addiction in adolescents, it was stated that the results of the studies carried out to reduce internet addiction in this period were positive (Bağatarhan & Siyez, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic study was conducted by Hamarta et al, (2021) using terms such as internet addiction, psychoeducation etc.. As a result of this study, it was concluded that the experimental attempts made on internet addiction were effective on one of the sub-dimensions of technology addiction. Considering the results of a systematic analysis examining the programs prepared to prevent internet addiction in adolescents, it was stated that the results of the studies carried out to reduce internet addiction in this period were positive (Bağatarhan & Siyez, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the use of technological products in adolescents has led to both positive and negative results. Among the positive results of the use of technological products, it is possible to mention these results: Faciliating the accessibility of information, providing the opportunity to examine the subjects and events in the course curriculum in three dimensions thanks to digital tools and providing the opportunity to be more understandable, positively affecting academic success, concretizing information by visualizing, faciliating communication and providing fast shopping etc.. (Hamarta et al, 2021). In addition, it is known that digital tools turned out to be effective in an uninterrupted, continuous education during the Covid19 pandemic.…”
Section: Introductionmentioning
confidence: 99%